International Financial Statistics, March 2018. (International Financial Statistics; International Financial Statistics ;, 2018)
This paper discusses that for countries that have introduced new currencies, the rates shown in International Financial Statistics (IFS) for the period before the introduction of the most recent currency may be used as conversion factors-they may be used to convert national currency in IFS to US dollar or SDR. In such cases, the factors are constructed by chain linking the exchange rates of the old and the new currencies. The basis used is the value of the new currency relative to the old currency, as established by the issuing agency at the time the new currency was introduced. Notes on the introduction of new currencies can be found in the Country Notes or in IFS print publication (if recent). Data on members' IMF accounts are presented in the Fund Position section in the country tables and in four world tables. Terms and concepts of IMF accounts and the time series in the country and world tables are explained below.